A2.20 ICOS-ICOSL interaction regulates lymphotoxin alpha expression and maturation of lymphoid-like stromal cells during inflammation. (13th February 2015) - Campos, J; Nayar, S; Chung, M; Hitchcock, JR; Withers, DR; Cunningham, AF; Carlesso, G; Herbst, R; Buckley, CD; Barone, F
Abstract : Background and Objectives: Costimulation Via ICOS-ICOSL Interaction is critical for germinal centre function in secondary lymphoid organs, enhancing T cell activation and maturation into cytokine-producing cells. In autoimmunity this signal has been extensively investigated and believed to contribute to the development of follicular T helper cells, autoimmune germinal centre B cells and abnormal autoantibody production. Blocking of ICOS-ICOSL interaction has been shown to amelliorate disease in animal models of systemic lupus erythematosus and rheumatoid arthritis. We used a novel model of ectopic lymphoneogenesis in adenoviral infected murine salivary glands to dissect the implications of ICOS-ICOSL interaction in T cell activation and consequent maturation of a subset of activated stromal cells in the formation of tertiary lymphoid organs (TLO). Methods: The submandibular glands of wild-type (wt) and knockout (KO) mice were intra-ductally cannulated with luciferase-encoding replication deficient adenovirus to induce TLO formation. A combination of experiments in ICOSL KO mice or blocking experiments, bone marrow chimaeras and in vitro mixed co-culture were performed to address ICOS/ICOSL interaction in this model. Results: We demonstrated that early post inflammatory insult ICOSL is significantly upregulated on a population of activated stromal cells that express gp38, adhesion molecules, TNFR1 and TNFR2. In vivo experiments in ICOSL knockout (KO) and blocking experiments, with an anti-ICOS blocking antibody, revealed a dramatic defect in TLO formation and reduced levels of ectopic lymphoid chemokines. We showed that engadgment of stromal derived ICOSL stimulates newly recruited effector T cells to produce lymphotoxin alpha (LTα) that in turn activates stromal cells via TNFR1 to produce lymphoid chemokines. These observations were further confirmed in vitro, in mixed co-cultures of lymphocytes, dendritic cells and stromal cells isolated from wt and ICOSL KO mice. Finally we validated this mechanism inducing TLO formation in ICOSL KO reconstituted with wt bone marrow. As predicted, ICOSLKO reconstituted with wt bone marrow showed a similar degree of impairment in the LTa/TNFR1 pathway as observed in the full KO. Discussion: Collectively, these data demonstrate that ICOSL expression by stromal cells supports the up-regulation of LTα on T cells in vivo and provide a novel mechanism of action between ICOSL on stromal cells, ICOS on T cells and LTα pathways in the context of TLO formation. Importantly, our work shows that both genetic and therapeutic blockade of ICOS-ICOSL interaction impairs TLO formation, highlighting an important role for stroma-derived ICOSL and a possible therapeutic target in TLO associated diseases.